Nurses to patients communication and barriers perceived by nurses at Tikur Anbessa Specilized Hospital, Addis Ababa, Ethiopia 2018 - Gbrekidan Wune; Yohannes Ayalew; Aklil Hailu; Tigistu Gebretensaye (Elsevier, 2020)
Background: Effective communication is defines as a two-way dialogue between two parties. Good nurses-patients communication is essential for successful individualized patient care outcome. Ineffective nurse-patient communication increases length of hospitalization, client dissatisfaction and resource wastage. Objective: The objective of the study was to assess level of nurse-patient communication and its barriers among nurses in the study area. Method: An institutional based cross-sectional study was conducted among 296 study participants at Tikur Anbessa specialized hospital between March 1st and March 30, 2018. A systematic random sampling technique was used to include study participants. A Semi-structured questionnaire was used to gather information from participants. Descriptive and analytical analysis including bivariate and multivariate analysis considering 95% CI was utilized to examine association between dependent and independent variables. P-value < 0.05 was considered statistically significant. Result: The level of effective nurse-patient communication in this study was34.5%. Lack of time and work overload were predominantly reported by nurses as the main barriers to effective nurses-patient communication. Time adequacy, engaging in multiple jobs and fatigue and family and friends at bed side were the factors associated with patient- nurse communication, AOR = 3.568[1.33-9.57], AOR = 5.621 [1.79-17.68], AOR = 7.122 [1.33-38.12] and AOR = 5.768 [2.04-16.33] respectively. Conclusion: This study showed that nurses-patient communication in the study area was low. Time, work load and fatigue and patient being with excess family members and friends were factors affecting effective patient-nurse communication. Standardized nurse to patient ratio, private and comfortable space arrangement may be necessary to ensure effective patient-nurse communication.